A Stable Manganese Pincer Catalyst for the Selective Dehydrogenation of Methanol. Issue 2 (2nd December 2016) - Andérez‐Fernández, María; Vogt, Lydia K.; Fischer, Steffen; Zhou, Wei; Jiao, Haijun; Garbe, Marcel; Elangovan, Saravanakumar; Junge, Kathrin; Junge, Henrik; Ludwig, Ralf; Beller, Matthias
Abstract: For the first time, structurally defined manganese pincer complexes catalyze the dehydrogenation of aqueous methanol to hydrogen and carbon dioxide, which is a transformation of interest with regard to the implementation of a hydrogen and methanol economy. Excellent long‐term stability was demonstrated for the Mn‐PNP i Pr catalyst, as a turnover of more than 20 000 was reached. In addition to methanol, other important hydrogen carriers were also successfully dehydrogenated. Abstract : Just a pinch : A molecularly defined manganese PNP pincer complex selectively dehydrogenates methanol to hydrogen and carbon dioxide at low temperature. Remarkable stability and an excellent turnover (TON) of more than 20 000 was achieved.